2012
DOI: 10.1638/2011-0081r.1
|View full text |Cite
|
Sign up to set email alerts
|

COMPARISON OF LARYNGEAL MASK AIRWAY USE WITH ENDOTRACHEAL INTUBATION DURING ANESTHESIA OF WESTERN LOWLAND GORILLAS (GORILLA GORILLA GORILLA)

Abstract: The laryngeal mask airway is an alternative to endotracheal intubation that achieves control of the airway by creating a seal around the larynx with an inflatable cuff. This study compared use of the laryngeal mask airway with endotracheal intubation in anesthetized western lowland gorillas (Gorilla gorilla gorilla). Eight adult gorillas were immobilized for routine and diagnostic purposes for a total of nine anesthetic events. During each anesthetic event, gorillas were either intubated (n = 4; group A) or fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 23 publications
1
8
0
Order By: Relevance
“…The v‐gel placement appeared to be technically easier and was faster than intubation, with a difference of about 42 seconds. These results are comparable with other SGAD studies performed in people, gorillas, rabbits, pigs, dogs and cats 18 22–27. Previous studies have shown that SGADs were consistently easier to place, even with researchers experienced in endotracheal intubation 17 21 28.…”
Section: Discussionsupporting
confidence: 87%
“…The v‐gel placement appeared to be technically easier and was faster than intubation, with a difference of about 42 seconds. These results are comparable with other SGAD studies performed in people, gorillas, rabbits, pigs, dogs and cats 18 22–27. Previous studies have shown that SGADs were consistently easier to place, even with researchers experienced in endotracheal intubation 17 21 28.…”
Section: Discussionsupporting
confidence: 87%
“…Prolonged recoveries after tiletamine-zolazepam, particularly at higher doses, have been reported, and after ketamine and detomidine in chimpanzees. 8,21 Despite widespread use of tiletamine-zolazepam in great apes, there is little data regarding the pharmacokinetics. Plasma halflives of tiletamine are reported to be between 1 and 1.5 hours for dogs, cats and monkeys, and between 1 and 8.4 hours for zolazepam in dogs, cats, rats, monkeys, pigs and polar bears.…”
Section: Discussionmentioning
confidence: 99%
“…Successful orotracheal intubation was facilitated by a brief period of isoflurane delivered in oxygen via a face mask. Other great ape anaesthetic protocols have used a volatile agent alone, 8 nitrous oxide and a volatile agent 18 or ketamine or tiletamine/zolazepam increments 19 to improve the plane of anaesthesia for intubation. No sudden arousals occurred during the procedures, but the addition of the volatile agent for maintenance facilitated unforeseen surgery and diagnostics during the health checks and ensured staff safety at all times.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Supraglottic airway devices (SADs), such as the laryngeal mask airway (LMA), form a seal around the larynx, usually with an inflatable cuff, providing the management of the airways intermediate between the facemask and endotracheal intubation, in terms of anatomic position, invasiveness, and safety [ 19 ]. The use of LMA is reported in NHPs such as chimpanzees, gorillas, and a gibbon [ 20 , 21 ], but no mention exists for baboons.…”
Section: Introductionmentioning
confidence: 99%